The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.sjbs.2021.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of rice bran lipase inhibition through fermentation activity of probiotic bacteria

Abstract: Rice bran oil is known as wonder oil and it is the most important vegetable oil in Asia. Rice bran oil is extracted from bran that is the outer hard layer of rice. It is an emerging category in edible oil with a lot of nutritional properties and health benefits. Rice bran oil is heart-friendly, boosts up immunity, and prevents from other diseases occurring commonly in Pakistan. The current study aimed to stabilize rice bran oil through different probiotic isolates and to assess the nutritional content of rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Dealcoholized apple juice sequentially fermented with Saccharomyces cerevisiae and L. plantarum improved obesity and fatty livers in mice on a high-fat diet better than unfermented apple juice [35]. However, only Hong et al [36] studied the potential of yogurt fermented with safflower extract to inhibit pancreatic lipase in vitro; Noureen et al [37] studied the inhibitory effect of fermented rice bran on lipase activity. Our previous study also found that SHLE fermented with L. fermentum grx08 significantly enhanced the anti-obesity efficacy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Dealcoholized apple juice sequentially fermented with Saccharomyces cerevisiae and L. plantarum improved obesity and fatty livers in mice on a high-fat diet better than unfermented apple juice [35]. However, only Hong et al [36] studied the potential of yogurt fermented with safflower extract to inhibit pancreatic lipase in vitro; Noureen et al [37] studied the inhibitory effect of fermented rice bran on lipase activity. Our previous study also found that SHLE fermented with L. fermentum grx08 significantly enhanced the anti-obesity efficacy [28].…”
Section: Discussionmentioning
confidence: 99%
“…51 Noureen et al have also reported that fermentation by Lactobacillus plantarum can stabilize rice bran by keeping an acidic pH value, which is not a suitable environment for rice bran lipase to catalyze the lipid (for the optimum pH value of rice bran lipase is 7.5−8.0). 23 Recently, Bolinedi et al reported that reducing the lipase or LOX expression, lowing the PUFA content (e.g., linoleic acid), or enhancing intrinsic antioxidants (e.g., γ-oryzanol) levels in rice bran through operating genome editing (e.g., CRISPR) on rice seeds is another promising approach in preventing rice bran rancidity. 17 These genetic and genome approaches are considered sustainable and costeffective; however, their development is still in its infancy.…”
Section: Stabilization Strategies Of Rice Branmentioning
confidence: 99%
“…Earlier, Vishwanath et al showed that lipase activity was completely inhibited, and the LOX activity was reduced by 50% after treatment with alcalase, but the viable nutrients and nutraceuticals were unaffected . Noureen et al have also reported that fermentation by Lactobacillus plantarum can stabilize rice bran by keeping an acidic pH value, which is not a suitable environment for rice bran lipase to catalyze the lipid (for the optimum pH value of rice bran lipase is 7.5–8.0) . Recently, Bolinedi et al reported that reducing the lipase or LOX expression, lowing the PUFA content (e.g., linoleic acid), or enhancing intrinsic antioxidants (e.g., γ-oryzanol) levels in rice bran through operating genome editing (e.g., CRISPR) on rice seeds is another promising approach in preventing rice bran rancidity .…”
Section: Stabilization Strategies Of Rice Branmentioning
confidence: 99%
See 1 more Smart Citation